TEACHER PERFORMANCE ASSESSED FROM WORK MOTIVATION, JOB SATISFACTION AND COMPENSATION IN SMP BATIK SURAKARTA - Galuh Pertiwi Rahmawati; Bambang Mursito; Istiatin Istiatin (JURNAL ILMIAH EDUNOMIKA, 2021)
Researchers conducted observations at SMP Batik Surakarta with the object of teacher research as a sample in order to determine the relationship between work motivation, job satisfaction and compensation with teacher performance. The research method is in the form of survey research using quantitative research with a sample size of about 48 teachers. The data collection method used a questionnaire with a saturated sampling technique. Processing of data using the SPSS program using multiple regression equation analysis tools. The results of the analysis can be obtained that the variables of motivation, job satisfaction and compensation have a simultaneous effect on the performance of teachers of SMP Batik Surakarta. Motivation has a significant effect on the performance of teachers in SMP Batik Surakarta. Job Satisfaction has a significant effect on the teacher performance of SMP Batik Surakarta. Compensation has a significant effect on the performance of teachers at SMP Batik Surakarta. The results of the observation show that simultaneously the independent variables which include work motivation, job satisfaction and compensation have a relationship with teacher performance. Keywords: Work Motivation; Job Satisfaction; Compensation with Teacher Performance